PENGARUH AIR REBUSAN DAUN KERSEN (MUNTINGIA CALABURA) TERHADAP PERUBAHAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS - zakiah zahra zakiah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Diabetes mellitus is increasingly prevalent and poses a health threat to the elderly. Patients often experience blood glucose instability. One management strategy is the use of herbal plants, namely boiled cherry guava leaves (Muntingia calabura), which contain saponins and flavonoids that inhibit blood sugar absorption in the intestines. Research Objective: To determine the effect of boiled jerry leaves (Muntingia calabura) on changes in blood glucose levels in diabetes mellitus patients.Research Method: This research uses a quantitative method with a pre-experimental one group pretest-posttest design, aiming to assess blood sugar level changes before and after the intervention using boiled cherry leaves. Research Results: The results show that in the first and tenth meetings, the asymp. Sig (2-tailed) is 0.001 < 0.005. This means Ha is accepted and Ho is rejected, indicating the effect of boiled cherry leaves on blood glucose changes in diabetes mellitus patients.Conclusion: The conclusion of this study is that the boiled water of cherry leaves (Muntingia calabura) affects changes in blood sugar levels in patients with diabetes mellitus in the Semangka Posyandu area, RW 008, Alam Jaya village. Keywords: Boiled Cherry Leaf Water (Muntingia Calabura), Blood Glucose, Diabetes Mellitus